Moving human rights beyond capitalism - Claudio Schuftan; Howard Waitzkin (Social Medicine Publication Group, 2023)
What do human rights mean when those who hold power and wealth throughout the world actually treat many of those beneath them as not fully human? The categorization of peoples as non-human, subhuman, or not fully human has appeared throughout human history. But this categorization has flourished especially since what has been called the "rosy dawn" of capitalism. Rooted in European capitalism, racism, imperialism, colonialism, neocolonialism, and patriarchy, the elites of capitalism have enslaved millions of people, mainly from Africa, and have exterminated millions more through genocide that wiped out indigenous populations, especially in the Americas and Asia. Slavery and genocide also have occurred within some imperialist countries of Europe, as fascist elites have used racist categorizations within their own realms. Racist ideas have justified these and other unacceptable conditions imposed on human beings considered less than human, while those not really human beings have generated immense wealth for elites intent to accumulate capital.